(untitled) (REVISTA NODO, 2024)
The exhibition is a manifesto of the continuity of Pablo Picasso’s legacy and its ability to endure in the contemporary art world. The exhibition offers a tour of some of the influences of the work of the creator of Guernica through 54 works by various Mexican artists. The project took as its starting point the fiftieth anniversary of the death of the Spanish painter Pablo Picasso (1881-1973).